2023
DOI: 10.1002/adsc.202201286
|View full text |Cite
|
Sign up to set email alerts
|

The Shuttle of Sulfur Dioxide: Iridium/Copper‐Cocatalyzed Trifluoromethylfluorosulfonylation of Alkenes

Abstract: Depending on the nature of the attached functional moiety, the sulfonyl radical can either undergo an automatic SO 2 liberation or react directly as the thermodynamically favored sulfonyl radical. Taking advantage of this unique property, we envisioned that through rational reaction design, the in situ release and re-insertion of SO 2 , i. e., the shuttle of SO 2 , can be realized. Herein we report our recent progress in copper metallaphotoredox cocatalyzed trifluoromethyl-fluorosulfonylation of alkenes with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Recently, the Xiao group reported a trifluoromethyl‐fluorosulfonylation reaction of alkenes with a new reagent, TFSP, as a competent source of both CF 3 radicals and SO 2 via copper/Ir(ppy) 3 co‐catalyzed photoredox pathway (Scheme 31). [48] This method provided an efficient and facile access to FSO 2 ‐containing molecules through SO 2 shuttle. Furthermore, this transformation could be well applied to a range of alkene substrates and showed a good tolerance to various functional groups as well as pharmaceutically relevant heterocycles.…”
Section: Radical Addition To Alkenylsulfonyl Fluoridesmentioning
confidence: 99%
“…Recently, the Xiao group reported a trifluoromethyl‐fluorosulfonylation reaction of alkenes with a new reagent, TFSP, as a competent source of both CF 3 radicals and SO 2 via copper/Ir(ppy) 3 co‐catalyzed photoredox pathway (Scheme 31). [48] This method provided an efficient and facile access to FSO 2 ‐containing molecules through SO 2 shuttle. Furthermore, this transformation could be well applied to a range of alkene substrates and showed a good tolerance to various functional groups as well as pharmaceutically relevant heterocycles.…”
Section: Radical Addition To Alkenylsulfonyl Fluoridesmentioning
confidence: 99%
“…The synthetic condition was mild, avoiding hazardous reagents and transition-metal catalysts (Scheme 58). The Xiao group [78] reported a novel SO 2 surrogate 59.1 and its application in sulfonylation-trifluoromethylation 59.2. Both sulfonyl and trifluoromethyl radicals came from the pyridinium salt 59.1.…”
Section: Othersmentioning
confidence: 99%
“…The Xiao group [78] reported a novel SO 2 surrogate 59.1 and its application in sulfonylation‐trifluoromethylation 59.2 . Both sulfonyl and trifluoromethyl radicals came from the pyridinium salt 59.1 .…”
Section: Thiolationmentioning
confidence: 99%
“…Based on the mechanistic investigation and our previous studies, , we propose a plausible mechanism, as shown in Scheme . The photoreductive cleavage of TFSP by the excited-state photocatalyst results in the formation of radical A , which then undergoes homolysis to produce DMAP and radical B .…”
mentioning
confidence: 94%
“…The imidazolium salt (IMDN-SO 2 CF 3 ), developed by Wang and his colleagues, has shown promising capabilities in enabling the C­(sp 3 )–H trifluoromethylation of azines and the trifluoromethylation-borylation of unsaturated hydrocarbons . Although the TFSP pyridinium salt was previously known, it was first developed as a trifluoromethylation reagent by our research team. , …”
mentioning
confidence: 99%